Dividend changes and future profitability changes – evidence from Polish listed companies - Kaźmierska-Jóźwiak, Bogna (Zmiany w zakresie dywidend a zmiany rentowności spółek notowanych na GPW w Warszawie, 2017)
The study attempts to extend the knowledge regarding the dividend policy of nonfinancial companies listed on the Warsaw Stock Exchange. In the previous part of the research the author analysed among others, determinants of dividend policy on the Polish capital market. The main aim of this paper, according to the dividend signalling theory, is to investigate whether the dividend changes convey some information about the future profitability of non-financial firms listed on the WSE paying dividends for at least two consecutive years. The study examines the relation between dividend changes and future profitability changes measured in terms of earnings per share payments of nonfinancial companies listed on the Warsaw Stock Exchange paying dividends in the 2007-2012 period using panel data analysis. The main hypothesis states that changes in dividends are positively correlated with changes of earnings in the year after the change in dividend. The research results show that firms that increase dividends are more profitable than firms that either decrease their dividends or do not make any changes in their dividend policy. Unpredictably, firms that cut dividends are more profitable than firms that leave dividends unchanged. The results of panel data analysis indicate that neither dividend increases, nor the dividend increases in the current year are related to future changes in earnings. Thus, the results do not support the hypothesis. To conclude, the current changes in dividends are not reliable signals of future earning changes one year ahead in the same direction
Ekonometria = Econometrics, 2017, Nr 4 (58), s. 95-104
Keywords: dividend; dividend policy; signaling theory; panel data analysis; dywidenda; polityka dywidend; teoria sygnalizacji; modele danych panelowych